Síntese e sinterização de pós-compósitos de aluminaboretos de alta dureza por moagem de alta energia - Cerqueira, Valdívio Rodrigues (Universidade Federal de São Carlos, 2014)
This work was aimed to obtain powder composite mixtures of ceramic phases with high hardness through high energy ball milling synthesis and characterization of sintered samples in terms of hardness. In an exploratory phase, many aluminothermic reactions were obtained from basic or precursors oxides such as WO3, TiO2, B2O3, Ti °, B ° and C, whose final products were B4C-TiB2-Al2O3 Al2O3 and (WB or WB2 or W2B5) - TiB2. The resulting powders from the processing of synthesis performed under different conditions were characterized employing the following techniques: X-ray diffraction (XRD), real density, X-ray fluorescence (XRF) and scanning electron microscopy (SEM). Two reactions were selected, where the powders were subjected to variation of milling time of high energy and disintegration procedure change. Samples of the powder were forming under uniaxial pressure of 50 MPa followed by isostatic pressure of 200MPa and sintered at 1600 °C, 1650 °C and 1700 °C under high vacuum aiming to characterize the microstructural evolution and microhardness Vickers. Thus, the results showed that the composite powder represented by Al2O3 - WB - TiB2 sintered at a temperature of 1700 °C allow to obtain apparent densities (% TD) and Vickers hardness, near 99% and 19 GPa respectively. The best results characterized by the density, microstructure and hardness were obtained by enhancing the grinding in ball mill and additional deagglomeration in planetary mill after high energy milling.
Synthesis and sintering of powder composite alumina-borides of high hardness by reactive milling
Keywords: Alumínio; Alumina-boretos; Moagem de alta energia; Síntese de pós-compósitos; Moagem reativa; Cerâmica de alta dureza; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA